Effect of adhesive techniques and preheated composite resin types as luting agents on shear bond strength of lithium disilicate: an experimental study - Damayanti, Asri; Untara, Raphael Tri Endra; Widyastuti, Andina (Universitas Padjadjaran, 2026)
Introduction: The success of veneers is influenced by the cementation procedure. Preheated composite resin has been proposed as a luting material for indirect adhesive restorations because of its improved mechanical and handling properties. Composite resin bonds effectively to tooth structures using adhesive systems. This study aimed to evaluate the effect of different adhesive application techniques and types of preheated composite resin as luting materials on the shear bond strength of lithium disilicate. Methods: Twenty-eight extracted maxillary premolars were prepared on the buccal surface to expose dentin and divided into four experimental groups. Lithium disilicate discs (3 mm in diameter and 1 mm in thickness) were cemented onto the prepared surfaces according to the assigned group protocols. Group IA received preheated microhybrid composite with total-etch adhesive, IB received self-etch adhesive; IIA received preheated nanohybrid composite with total-etch adhesive, and IIB received self-etch adhesive. After cementation, the samples were immersed in artificial saliva at 37oC for 24 hours. Shear bond strength testing was conducted using a universal testing machine. Debonded samples were observed under a stereomicroscope to determine bonding failure. Data were analyzed using two-way ANOVA and post hoc LSD tests with a 95% confidence level. Results: Total-etch adhesive demonstrated higher shear bond strength (SBS) than self-etch adhesive for both composite types. The highest SBS was observed in the total-etch microhybrid group (14.03 ± 0.12 MPa), followed by the total-etch nanohybrid group (12.99 ± 0.09 MPa) and the self-etch microhybrid group (13.67 ± 0.18 MPa), while the lowest value was recorded in the self-etch nanohybrid group (10.21 ± 0.22 MPa) Conclusion: Preheated microhybrid composite resin produced higher shear bond strength with lithium disilicate than preheated nanohybrid composite resin, and the total-etch adhesive technique resulted in higher shear bond strength than the self-etch technique.